Predictors of Outcome in Adenoid Cystic Carcinoma of Salivary Glands: a Clinicopathologic Study with Correlation between MYB Fusion and Protein Expression - Xu, Bin (Am J Surg Pathol, 2017)
Adenoid cystic carcinoma (ACC) is the second most common salivary gland malignancy and it has a high rate of recurrences and a poor long term prognosis. Our aim was to assess the prognostic factors in ACC and study MYB-NFIB fusion and MYB protein expression in a large retrospective cohort of 135 patients with a median follow up of 6.3 years. The 5-year and 10-year local recurrence-free survival rate of 94% and 78%, 5-year and 10-year distant metastasis survival rate of 77% and 58%, and 5-year and 10-year recurrence free survival (RFS) of 66% and 44%. The following features were identified as adverse prognostic factors of RFS on univariate analysis: large tumor size, solid growth pattern, increased mitoses, positive margin, AJCC clinical staging, high grade transformation, vascular invasion, nuclear atypia, open chromatin, prominent nucleoli, and tumor necrosis. However, on multivariate analysis, only increased mitoses (≥5/10 high power fields), any solid growth pattern, and advanced AJCC TNM staging were independent adverse predictors for RFS. MYB immuno-expression and MYB-NFIB translocation were common findings in ACC, occurring in 72% and 59% of the tested ACCs, respectively. The sensitivity and specificity of MYB immunohistochemistry in detecting MYB-NFIB fusion was relatively low at 78% sensitivity and 50% specificity. The high prevalence of alterations leading to high expression of the MYB transcription factor family suggests that targeted approaches developed to suppress the expression of these oncogenic transcription factors and/or the transcriptional activity of these proteins would be a rational therapeutic approach to investigate in ACC.